ANXA1: An Important Independent Prognostic Factor and Molecular Target in Glioma - Zhang, Dongdong; Wang, Wenyan; Zhou, Huandi; Su, Linlin; Han, Xuetao; Zhang, Xinyuan; Han, Wei; Wang, Yu; Xue, Xiaoying (Frontiers in Genetics, 2022)
Objective: The expression, prognosis and related mechanism of ANXA1 is investigated in glioma, with the purpose that to find potential therapeutic molecular targets for glioma. Methods: We analyzed the gene expression of ANXA1 using glioma-related databases, including the Chinese Glioma Genome Atlas (CGGA) database, The Cancer Genome Atlas (TCGA) database and the Gene Expression Omnibus (GEO) database. Meanwhile, we collected the sample tissues and corresponding paracancerous tissues of 23 glioma patients, then conducted Western blot experiment to verify the expression and correlate survival of ANXA1. Moreover, we generated survival ROC curves, performing univariate and multivariate Cox analysis and the construction of the Nomogram. Differential expression analysis was conducted by high and low grouping based on the median of ANXA1 gene expression values. We conducted Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis and gene set enrichment analysis (GSEA) to explore possible mechanisms and gene co-expression analysis was also be performed. Results: The results showed that ANXA1 expression level was higher in gliomas than normal tissues, and high expression level of ANXA1 in gliomas was associated with poorer prognosis. The independent prognosis analysis showed that the ANXA1 gene was an independent prognostic factor of glioma. In the analysis of KEGG and GSEA, it is shown that ANXA1 may play an important role in glioma patients by affecting extracellular matrix (ECM)-receptor interaction and the focal adhesion signal pathway. The core genes, including COL1A1, COL1A2, FN1, ITGA1 and ITGB1, were screened for gene correlation and prognosis analysis. The expression level of five genes was verified by qPCR in glioma. we concluded that these five core genes and ANXA1 could play a synergistic role in gliomas. Conclusion: The results indicated that high expression level of ANXA1 leads to a worse prognosis, and ANXA1 is an independent prognostic factor and a potentially important target of the treatment in gliomas.